2021
DOI: 10.1136/bmjopen-2021-053916
|View full text |Cite
|
Sign up to set email alerts
|

Establishing best practices in cancer online support groups: protocol for a realist review

Abstract: IntroductionConsiderable observational evidence suggests that cancer online support groups reduce feelings of isolation, depression and anxiety, enhance coping and self-management, and lead to better informed patients. Other studies indicate that cancer online support groups can increase distress. Yet no studies theorise the complex, context-dependent mechanisms by which cancer online support groups generate their—sometimes contrasting—outcomes.Methods and analysisGuided by an integrated knowledge translation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 52 publications
(80 reference statements)
0
10
0
Order By: Relevance
“…Cancer support groups have been shown to result in a higher quality of life in cancer survivors [ 40 ], reducing the psychological symptoms of cancer survivorship and aiding in cancer-related self-management [ 41 ]. This was echoed by the findings of this study, with those that attended support groups finding them extremely useful.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer support groups have been shown to result in a higher quality of life in cancer survivors [ 40 ], reducing the psychological symptoms of cancer survivorship and aiding in cancer-related self-management [ 41 ]. This was echoed by the findings of this study, with those that attended support groups finding them extremely useful.…”
Section: Discussionmentioning
confidence: 99%
“…Online cancer support group (OCSG) participants are composed of heterogeneous members who are generally younger and have higher levels of education compared to face-toface support groups [14][15][16]. Moreover, OCSGs provide several advantages to promote communication between cancer patients, as its members share different communication subjects and goals [16].…”
Section: Introductionmentioning
confidence: 99%
“…Online cancer support group (OCSG) participants are composed of heterogeneous members who are generally younger and have higher levels of education compared to face-toface support groups [14][15][16]. Moreover, OCSGs provide several advantages to promote communication between cancer patients, as its members share different communication subjects and goals [16]. This is particularly true in South Korea, where there is increased diversity in OCSG member composition with Internet penetration in over 95% [17], which can swiftly disseminate the anti-cancer anthelmintic issue through Internet-based media.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that cancer peer support for adult patients is an effective complement to professional health care, foremost by providing psychosocial relief and addressing unmet support needs of cancer patients, specifically those related to their daily life 14–17 . It fosters the empowerment of cancer patients to cope better with their disease and to find ways and solutions for adequate self‐management 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…13 Research has shown that cancer peer support for adult patients is an effective complement to professional health care, foremost by providing psychosocial relief and addressing unmet support needs of cancer patients, specifically those related to their daily life. [14][15][16][17] It fosters the empowerment of cancer patients to cope better with their disease and to find ways and solutions for adequate selfmanagement. 18,19 The main resource of nonprofessional psychosocial support are cancer self-help groups (SHGs) which are peer support groups of individuals with the same disease who meet outside professional settings in nonhierarchical relationships on a voluntary basis.…”
mentioning
confidence: 99%